2004
DOI: 10.1111/j.0022-1112.2004.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differences between two sympatric morphs of Arctic charr confirmed by microsatellite DNA

Abstract: Significant genetic differences (F ST ¼ 0Á032) were found between littoral and profundal morphs of Arctic charr Salvelinus alpinus from Fjellfrøsvatn, northern Norway, using microsatellite DNA analysis. The morphs had strong reproductive isolation in time and space; the segregation of a separate profundal morph is rare in postglacial lakes. # 2004 The Fisheries Society of the British Isles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 41 publications
6
51
0
Order By: Relevance
“…We used the primers Smm_22 and Smm_24, which were isolated and characterized from other salmonid species by Crane et al (2004). We chose these primers based on a previous study from the same population, which demonstrated high polymorphism at these loci ( Table 1 in Westgaard et al, 2004). This analysis of the 32 parents gave 16 and 13 different alleles at Smm_22 and Smm_24, respectively, whereas the numbers of different alleles counted in males only were 15 and 12 at the two loci, respectively.…”
Section: Pcrmentioning
confidence: 99%
“…We used the primers Smm_22 and Smm_24, which were isolated and characterized from other salmonid species by Crane et al (2004). We chose these primers based on a previous study from the same population, which demonstrated high polymorphism at these loci ( Table 1 in Westgaard et al, 2004). This analysis of the 32 parents gave 16 and 13 different alleles at Smm_22 and Smm_24, respectively, whereas the numbers of different alleles counted in males only were 15 and 12 at the two loci, respectively.…”
Section: Pcrmentioning
confidence: 99%
“…Kahilainen and Østbye 2006;Knudsen et al 2006;Vonlanthen et al 2009;Siwertsson et al 2013b) and along the pelagic zone (Helland et al 2008;Ohlberger et al 2008a, b) with clear thermal differences between the preferred habitats in the wild. Deepwater morphs of postglacial fishes may differ genetically from their sympatric upper-water morphs (Westgaard et al 2004;Praebel et al 2013) and may display inherited deep-water adaptations (i.e. behaviour and morphology) related to resource acquisition (Klemetsen et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…November 25 to January 15) of polar night at this latitude. The study lake harbours two different morphs of Arctic charr, one littoral spawning morph (L-morph) and one profundal spawning, dwarf-like morph (P-morph) that differ distinctly in their ecology, morphology and genetics (Klemetsen et al 1997(Klemetsen et al , 2002Westgaard et al 2004;Knudsen et al 2006Knudsen et al , 2007Amundsen et al 2008). The L-morph charr resemble the Arctic charr populations found in other lakes in the region (Klemetsen et al 1997;Knudsen et al 2006), whereas the dwarfed P-morph charr appear to be confined to a rare and untypical ecological niche for the species, residing their whole life in the profundal zone and feeding on typical profundal prey from the soft-bottom sediments (Klemetsen et al 1997(Klemetsen et al , 2002(Klemetsen et al , 2003aKnudsen et al 2006;Amundsen et al 2008).…”
Section: Introductionmentioning
confidence: 99%